PENGARUH PEMBERIAN PUPUK ANORGANIK DAN KONSENTRASI PUPUK ORGANIK CAIR PADA PERTUMBUHAN SETEK LADA (Piper nigrum L) - Netty Syam; Saida Saida; Cahyo Wicaksona (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2020)
This research was carried out at the Darul Mukhlisin Islamic Boarding School in Padang Lampe, Muslim University of Indonesia, Pangkep Regency, South Sulawesi, which took place from March to September 2019. The study was aimed at analyzing the effect of the composition of N: P: K on the growth of pepper seedlings, analyzing the effect of the concentration of Organic Fertilizers Liquid (POC) on the growth of pepper seedlings, analyzing the interaction between giving the composition of N: P: K and giving POC on the growth of pepper seedlings. This research was compiled using a Randomized Group Design (RBD) consisting of two factors. The first factor is the composition of N: P: K consisting of: N: PK 1 : 0 : 0 / plant, N: P: K 1 : 1 : 1 / plant, N: P: K 2 : 1 : 1 / plant and N : P: K  2 :1 : 2 / plant. The second factor is the concentration of Liquid Organic Fertilizer consisting of no POC, POC 0.05% / liter of water, POC 0.10% / liter of water and POC 0.15% / liter of water. The results showed that the best effect on the use of the composition N: P: K on the length of the shoot, number of leaves and leaf area of pepper seedlings. The use of liquid organic fertilizer concentration of 0.10% / liter of water gives the best effect on shoot length, number of shoots, and number of leaves and leaf area, and there are significant interactions between the composition factors of N: P: K and POC concentration on the shoot length variable of pepper seedling growth.